Longwave radiation budget at the Baltic Sea surface from satellite and atmospheric model data - Tomasz Zapadka (Oceanologia, 2008)
The net longwave radiation flux LW↑↓ in the Baltic Sea in 2001 has beensubjected to spatial and temporal analysis. Maps of the mean monthlyLW↑↓ over the Baltic were drawn using the new semi-empirical formula for the Baltic Sea (Zapadka et al. 2007).The input data for the formula, such as sea surface and air temperatures,and cloud cover, were obtained from the Tiros N/NOAA and METEOSAT 7 satellites and from the UMPL forecast model (see http://meteo.icm.edu.pl). The mean annual LW↑↓for 2001 was estimated at 63 W m-2 and compared with available data from other sources. The monthly maps of the net flux LW↑↓ over the Baltic show that the total valuesreach a minimum (LW↑↓ ≈ 50 W m-2) in April, September, October and a maximum (LW↑↓ ≈ 80 W m-2) in November.The statistical error of daily maps, on which the monthly maps were based, is no more than 18 W m-2.